Determination of zeolite-group mineral compositions by electron probe microanalysis. (2nd January 2018) - Campbell, L. S.; Charnock, J.; Dyer, A.; Hillier, S.; Chenery, S.; Stoppa, F.; Henderson, C. M. B.; Walcott, R.; Rumsey, M.
Abstract: A new protocol for the quantitative determination of zeolite-group mineral compositions by electron probe microanalysis (wavelength-dispersive spectrometry) under ambient conditions, is presented. The method overcomes the most serious challenges for this mineral group, including new confidence in the fundamentally important Si-Al ratio. Development tests were undertaken on a set of natural zeolite candidate reference samples, representing the compositional extremes of Na, K, Cs, Mg, Ca, Sr and Ba zeolites, to demonstrate and assess the extent of beam interaction effects on each oxide component for each mineral. These tests highlight the variability and impact of component mobility due to beam interaction, and show that it can be minimized with recommended operating conditions of 15 kV, 2 nA, a defocused, 20 μm spot size, and element prioritizing with the spectrometer configuration. The protocol represents a pragmatic solution that works, but provides scope for additional optimization where required. Vital to the determination of high-quality results is the attention to careful preparations and the employment of strict criteria for data reduction and quality control, including the monitoring and removal of non-zeolitic contaminants from the data (mainly Fe and clay phases). Essential quality criteria include the zeolite-specific parameters of R value (Si/(Si + Al + Fe 3+ ), the ' E %' charge-balance calculation, and the weight percent of non-hydrous total oxides. When these criteria are applied in conjunction with the recommended analytical operating conditions, excellent inter-batch reproducibility is demonstrated. Application of the method to zeolites with complex solid-solution compositions is effective, enabling more precise geochemical discrimination for occurrence-composition studies. Phase validation for the reference set was conducted satisfactorily with the use of X-ray diffraction and laser-ablation inductively-coupled plasma mass spectroscopy.